2017 IEEE 86th Vehicular Technology Conference (VTC-Fall) 2017
DOI: 10.1109/vtcfall.2017.8288259
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Hazard Symbol Detection and Localization Using UAV Imagery

Abstract: Abstract-Unmanned Aerial Vehicle (UAV) technology is advancing at a fast pace following the strong rise in interest in its applications for a wide variety of scenarios. One of the promising use cases for UAVs is their deployment during emergency and rescue operations. Their high mobility, aerial viewpoint and flexibility to be operated autonomously are huge assets during crises. UAVs exist in a wide range when it comes to cost, and so do the sensors or accessories they can carry along as payload. During emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The trained model is also able to detect occluded, overlapped, and partially visible signs. The experimental results showed that the DeepHAZMAT model is more accurate and faster than many other recent and state-or-the-art research works such as [18], [19], and [20]. The developed DNN-based system was fast enough to be implemented in Mobile robots, using a single Intel NUC Corei7 embedded system for robust and real-time hazard label detection, recognition, identification, localisation, and segmentation, thanks to skipping redundant input frames as well as adaptation of the YOLOv3-tiny for our real-time robotics application.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The trained model is also able to detect occluded, overlapped, and partially visible signs. The experimental results showed that the DeepHAZMAT model is more accurate and faster than many other recent and state-or-the-art research works such as [18], [19], and [20]. The developed DNN-based system was fast enough to be implemented in Mobile robots, using a single Intel NUC Corei7 embedded system for robust and real-time hazard label detection, recognition, identification, localisation, and segmentation, thanks to skipping redundant input frames as well as adaptation of the YOLOv3-tiny for our real-time robotics application.…”
Section: Discussionmentioning
confidence: 88%
“…Nils et al [19], train a deep neural network model based on the YOLOv2 algorithm for hazmat sign detection. Although their model performs fast on a GPU platform, their model is not real-time on CPUs and the system has an error of up to 1.5" in localising the hazmat signs.…”
Section: Deep Learning Based Methodsmentioning
confidence: 99%
“…Preferably we want a solution that doesn't require a complex on-board setup (LiDAR or other expensive and/or heavy imaging system) to minimize cost and maximize flight time. Tijtgat et al [25] present a solution that matches this requirement and provides a positional accuracy of <1.5m. The work presented in [13] proposes a vision-based UAV approach and landing scenario.…”
Section: Object Positioning Algorithmmentioning
confidence: 99%
“…The Cascaded-CNN (C-CNN) model has been implemented with the TX2 and applied to the classification of weeds in multi-spectral images in intelligent agriculture. These studies [23][24][24][25] [26] have shown that the embedded hardware of the Jetson series is effective in target detection and has the advantages of having high efficiency and low power consumption.…”
Section: Applying Edge Computing To Deep Learningmentioning
confidence: 99%